A review of the systematics of small mammalian carnivores. Issue 1 (6th August 2020) - Veron, G.
Abstract : Small mammalian carnivores represent over half of the species of the order Carnivora. Over the past few decades, molecular studies have improved the systematics of small carnivore families, resulting in the recognition of four additional families. Several new species of small carnivores have also been proposed recently, but some of these have not been validated by genetic data. Studies of intraspecific genetic polymorphism and structure have helped in the process of defining conservation units, which is crucial for the management of zoo populations. Abstract : Small mammalian carnivores represent over half of the species of the order Carnivora. Over the past few decades, molecular studies have improved the systematics of small carnivore families, resulting in the recognition of four additional families. Several new species of small carnivores have also been proposed recently but some of these have not been validated by genetic data. Studies of intraspecific genetic polymorphism and structure have helped in the process of defining conservation units, which is crucial for the management of zoo populations. (Photo: Golden palm civet Paradoxurus zeylonensis, National Zoological Gardens of Sri Lanka. Géraldine Veron, Muséum National d'Histoire Naturelle Paris)